2009
DOI: 10.3181/0809-rm-285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diesel Exhaust Particles on Antigen-Presenting Cells and Antigen-Specific Th Immunity in Mice

Abstract: Diesel exhaust particles (DEP) exacerbate antigen-related airway inflammation and hyperresponsiveness in mice; however, the mechanisms remain undefined. The present study characterized more precisely which pathways and cellular events of the allergic response are amplified by DEP in view of the maturation/activation/function of antigen-presenting cells (APC) and the antigen-specific Th response. We evaluated the effects of DEP on the phenotype and function of bone marrow-derived dendritic cells (BMDC) in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 45 publications
5
29
0
4
Order By: Relevance
“…In addition, one intriguing aspect of the epidemiologic data is that health effects of PM 2.5 are primarily seen in subjects with predisposing factors, including pneumonia, asthma, chronic obstructive pulmonary disease, compromised immune systems, and age over 65 years old [3]. Consistent with the epidemiological studies, we have experimentally demonstrated that diesel exhaust particles (DEP), major contributors to environmental PM 2.5 in urban areas, exhibit respiratory toxicity with or without predisposing factors in vivo [4][5][6][7][8][9][10].…”
Section: Introductionsupporting
confidence: 61%
See 1 more Smart Citation
“…In addition, one intriguing aspect of the epidemiologic data is that health effects of PM 2.5 are primarily seen in subjects with predisposing factors, including pneumonia, asthma, chronic obstructive pulmonary disease, compromised immune systems, and age over 65 years old [3]. Consistent with the epidemiological studies, we have experimentally demonstrated that diesel exhaust particles (DEP), major contributors to environmental PM 2.5 in urban areas, exhibit respiratory toxicity with or without predisposing factors in vivo [4][5][6][7][8][9][10].…”
Section: Introductionsupporting
confidence: 61%
“…The concentration of particulate matter (PM) with mass median aerodynamic diameter (a density-dependent unit of measure used to describe the diameter of the particle) B2.5 lm (PM 2.5 ) is more closely associated with both acute and chronic respiratory effects and subsequent mortality than larger particles of B10 lm (PM 10 ) [2]. In addition, one intriguing aspect of the epidemiologic data is that health effects of PM 2.5 are primarily seen in subjects with predisposing factors, including pneumonia, asthma, chronic obstructive pulmonary disease, compromised immune systems, and age over 65 years old [3].…”
Section: Introductionmentioning
confidence: 99%
“…One could therefore speculate that DEP exposure has an impact on several aspects of the DC biology. Indeed, in vitro data demonstrated that DEP exposure induces DC maturation (10,11) via epithelial cell-derived mediators (12,13) and that DEP-exposed DCs induce a Th2 polarization (10,(13)(14)(15).…”
Section: Once Arrived In the Mln Dcs Present The Ags To Naive T Cellmentioning
confidence: 99%
“…47) In our previous study, the numbers of cells expressing MHC class II and/or co-stimulatory molecules (CD80 and CD86) in the lung were greater in the DEP+OVA group than in the other groups. 41) Furthermore, the numbers of DC, macrophages, and B cells bearing MHC class II in the lung were also increased by the administration of DEP to antigen-sensitized mice. It can be proposed that the enhanced expression of these APC-related molecules and increased pulmonary numbers of APC in the presence of antigen induced by DEP can, at least in part, play a role in the aggravating eŠects of DEP on the allergic response in the airway as reported previously.…”
Section: Dep On Dc-t Cell Axismentioning
confidence: 93%
“…32,33,36,37) Several studies have identiˆed a critical role for DC in antigen-related airway in‰amma-tion. 38,39) Indeed, in vitro data demonstrated that DEP exposure induces DC maturation 40,41) via epithelial cell-derived mediators 42,43) and that DEP-exposed DC induce a Th2 polarization. 40,44,45) On the other hand, proallergic eŠects of DEP on T lymphocytes primed with in vivo antigen challenge remain obscure, although previous in vivo studies have demonstrated that DEP amplify the lung expression of Th cytokines.…”
Section: Dep On Dc-t Cell Axismentioning
confidence: 99%